An annotated checklist of the Amphipoda (Crustacea) of Kuwait, north-western Arabian Gulf - Al-Kandari, Manal; Polikarpov, Igor; Nithyanandan, Manickam; Al-Yamani, Faiza; Grintsov, Vladimir (Zootaxa, 2023)
Kuwait’s intertidal and subtidal habitats were surveyed from 2013 to 2016 for amphipods, and earlier records from Kuwait and the rest of the Gulf were compared to provide the first annotated checklist of Amphipoda in Kuwait. A total of 82 sites in mainland and islands were surveyed including intertidal and subtidal zones. The resulting data identified 86 amphipod taxa belonging to 54 genera, 32 families and 3 suborders, including 20 new records to science that are currently being described. A total of 46 amphipod species, 34 genera and 19 families constituted new regional records either for Kuwait or the entire Gulf area. Information on local distribution, occurrence, and habitat are provided for each species. Within the tidal zonation, 50 species inhabited both the intertidal and subtidal areas, 19 were intertidal, 12 subtidal, and 3 species were found in the supratidal zone. Sandy and rocky shores supported the most diverse amphipod assemblages. A gradient of increasing amphipod species richness from north to south along Kuwait’s mainland coastline was revealed. The high level of regional endemism supported notable taxonomic distinction of the amphipod fauna of Kuwait from the other Gulf areas. Compositional dissimilarity among amphipod faunas increased with distance within a wide longitudinal gradient across the Gulf, Sea of Oman, and north-western Arabian Sea.